Hexavalent chromium leads to differential hormetic or damaging effects in alfalfa (Medicago sativa L.) plants in a concentration-dependent manner by regulating nitro-oxidative and proline metabolism. (December 2020) - Christou, Anastasis; Georgiadou, Egli C.; Zissimos, Andreas M.; Christoforou, Irene C.; Christofi, Christos; Neocleous, Damianos; Dalias, Panagiotis; Torrado, Sofia O.C.A.; Argyraki, Ariadne; Fotopoulos, Vasileios
Abstract: Chromium has been proven to be extremely phytotoxic. This study explored the impacts of increasing Cr(VI) exposure (up to 10 mg L −1 K2 Cr2 O7 ) on the growth and development of alfalfa plants and adaptation responses employed, in an environmentally relevant context. The threshold concentration of K2 Cr2 O7 in irrigation water beyond which stress responses are initiated is 1 mg L −1 . Lower Cr(VI) exposure (0.5 mg L −1 K2 Cr2 O7 ) induced hormesis, evident through increased biomass and larger leaves, likely mediated by increased NO content (supported by elevated NR enzymatic activity and overexpression of NR and ndh genes). Elevated Cr(VI) exposure (5 and 10 mg L −1 K2 Cr2 O7 ) resulted in reduced biomass and smaller leaves, and lower levels of photosynthetic pigment (10 mg L −1 K2 Cr2 O7 ). Higher levels of lipid peroxidation, H2 O2 and NO contents in these plants suggested nitro-oxidative stress. Stress responses included increased SOD and CAT enzymatic activities, further supported to some extent by MnSOD, FeSOD, Cu/ZnSOD and CAT transcripts levels. GST7 and GST17 gene expression patterns, as well as proline content, P5CS enzymatic activity and corresponding P5CS and P5CR gene expression levels emphasized the role of proline and GSTs in the adaptation responses. Results highlight the importance of managing Cr(VI) levels in irrigation water. Graphical abstract: Image 1 Highlights: Alfalfa plants were exposed to Cr(VI) through irrigation in an agricultural setting. Low exposure (0.5 mg L −1 K2 Cr2 O7 ) induced hormesis, mediated by elevated NO content. Phytotoxic effects are initiated when K2 Cr2 O7 in irrigation water exceeded 1 mg L −1 . Elevated Cr(VI) exposure (5, 10 mg L −1 K2 Cr2 O7 ) resulted in nitro-oxidative stress. Accumulation of proline and GSTs leads to enhanced tolerance to Cr(VI) toxicity.